تسليط الضوء على أثر الدافع بين الطلبة غير المشاركين - الشريف, أكرم محمد (Al-Qurtas, 2025)
In the Libyan context, where English is taught as a foreign language, the challenges of cultivating motivation among EFL learners are especially enunciated. The English Department at the Faculty of Languages at Tripoli University, like many other institutions in Libya, faces significant difficulties in encouraging the indolent students to be engaged in EFL classrooms. Despite the importance of English language proficiency for Libyan students, many struggle to develop and maintain the motivation necessary to achieve their language learning goals. This study aims to explore the internal and external factors that influence motivation among the passive, including lack of interest, fear of failure, teacher support, and classroom dynamics. A mixed-methods approach was employed, combining both quantitative and qualitative data collection and analysis methods. A questionnaire was administered to a sample of 60 passive students, and semi-structured interviews were conducted with a subsample of 20 passive students. The analysis reveals that internal factors, such as lack of interest and fear of failure, and external factors, such as teacher support and classroom dynamics, play a significant role in influencing motivation among the passive students. The study's findings have promising implications for teachers, policymakers, and researchers seeking to enhance motivation and engagement among EFL learners. The study highlights the importance of teacher support and training, and the need to foster positive classroom dynamics to boost motivation and engagement among the passive students. This study contributes to the existing body of knowledge on motivation in EFL classrooms, and provides insights for educators and policymakers seeking to promote motivation and engagement among EFL learners in similar contexts.